2020
DOI: 10.3390/md18080402
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity of Mycalin A and Its Analogues on Human Skin Melanoma and Human Cervical Cancer Cells

Abstract: Mycalin A, a polybrominated C15 acetogenin isolated from the encrusting sponge Mycale rotalis, displays an antiproliferative activity on human melanoma (A375) and cervical adenocarcinoma (HeLa) cells and induces cell death by an apoptotic mechanism. Various analogues and degraded derivatives of the natural substance have been prepared. A modification of the left-hand part of the molecule generates the most active substances. A structurally simplified lactone derivative of mycalin A, lacking the C1–C3 side chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The relative configurations of 9a–9d were unambiguously identified by the 1 H NMR coupling constant analysis, the correlated spectroscopy spectra, and the nuclear Overhauser effect spectroscopy spectra (see Supporting Information S182–S187 for more details). It should be noted that 9a–9d are also ubiquitous key motifs in numerous natural products and pharmaceutically active substances such as dactylopyranoid, thyrsenol A, 8-acetylcaespitol, caespitol, caespitane, calyculin J, laureepoxide, and mycalin A, among others . Moreover, 2za and 2zb were both readily obtained with excellent enantioselectivities via the ATH of the corresponding diketones, and through simple further transformations, drug molecules ibuprofen and naproxen were produced in moderate total yields with 94% ee and 95% ee, respectively (Scheme f,g).…”
Section: Resultsmentioning
confidence: 99%
“…The relative configurations of 9a–9d were unambiguously identified by the 1 H NMR coupling constant analysis, the correlated spectroscopy spectra, and the nuclear Overhauser effect spectroscopy spectra (see Supporting Information S182–S187 for more details). It should be noted that 9a–9d are also ubiquitous key motifs in numerous natural products and pharmaceutically active substances such as dactylopyranoid, thyrsenol A, 8-acetylcaespitol, caespitol, caespitane, calyculin J, laureepoxide, and mycalin A, among others . Moreover, 2za and 2zb were both readily obtained with excellent enantioselectivities via the ATH of the corresponding diketones, and through simple further transformations, drug molecules ibuprofen and naproxen were produced in moderate total yields with 94% ee and 95% ee, respectively (Scheme f,g).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the lactones 8 and 9 were the most selective compounds, showing a limited killing effect towards the HDF cells ( 8 : 50%; 9 : 40%). Compound 4 , on the contrary, showed a rather limited selectivity causing a 70% death of the HDF cells, a value which is not unlike that shown against the HeLa and WM266 tumor cells, but is higher than that shown by the original lactone 3 on the HDF cells that displayed a 30% killing effect [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mycalin A ( 1 , Figure 1 ) is a polybrominated C 15 acetogenin [ 1 ] isolated some years ago in our group from the encrusting sponge Mycale rotalis [ 2 , 3 ]. As a continuation of our interest in the search for new anti-tumor substances, either of synthetic or natural origin [ 4 , 5 , 6 ], we recently reported that mycalin A displays strong antiproliferative activity on human melanoma (A375) and human cervical adenocarcinoma (HeLa) cells ( Figure 1 and Table 1 ) [ 7 ]. Nevertheless, mycalin A also showed a strong cytotoxicity towards human dermal fibroblasts (HDF) used as healthy control cells ( Figure 1 and Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors postulate that this cytotoxic effect is executed via the MAPK/ERK pathway, as well as by the activation of the Nur77 nuclear receptor activity [ 37 ]. Capasso et al showed an antiproliferative activity and selectivity of mycalin A and its derivatives, synthesized by the same group, in melanoma and cervical cancer models [ 38 ]. Shubina and colleagues reported the discovery of a new structural group of spongian monosulfated polyoxygenated steroids named gracilosulfates.…”
mentioning
confidence: 99%